OPTIMASI PARAMETER PROSES VACUUM ASSISTED RESIN INFUSSION TERHADAP SIFAT FISIK DAN MEKANIK KOMPOSIT POLYESTER FIBER GLASS - Dani Arief Bahtiar; Hari Arbiantara (ROTOR, 2016)
Vacuum assisted resin infusion is a method which was used to manufacture composite review. The method of vacuum assisted resin infusion (VARI) method using inversely proportional to non-vacuum methods. Requires singer method air-room safe hearts printing. VARI process can be reducing the effects of fouling that much happens on as non vacuum processes which raises less than optimal properties of composite materials. Problems That study is to determine review process parameter optimization of vacuum assisted resin infusion against physical and mechanical properties of composite polyester fiber glass. Knowing the influence of vacuum pressure treatment and hardening of composite processing time in the manufacturing process of composite with VARI method in the physical and mechanical testing of surface roughness, tensile and impact. Variations were used that vacuum pressure of 0.2; 0.5; 1.0 bar and a hardening of composite 2 hours; 4 hours; 6 hours. From the research VARI composite manufacturing method, surface roughness values obtained, the tensile strength and the best impact occurs at various pressure of 0.2 bar and a time of 2 hours hardening composite has a value of 0.498 μm surface roughness, the value of 27.344 MPa tensile test and impact test values 47.859 J / mm2.